2022
DOI: 10.1097/nmd.0000000000001464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Cognitive Functions in Patients With COVID-19 Infection

Abstract: In December 2019, some pneumonia cases emerged in Wuhan, China.It was named as Coronavirus 2019 (COVID-19) by the World Health Organization.Patients developed anxiety and sleep problems after treatment. Patients with confirmed COVID-19 (n = 57) admitted to our study and whose treatment was completed 3 months ago were included in the study. This is a case-control study, and 22 patients included the control group. We found statistical significance between the average score of Beck anxiety and Pittsburgh Sleep Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Our results also showed that the effects of COVID-19 infection on cognitive performance and functions were weak; a finding that was in disagreement with the former studies that reported significant adverse effects of both mild and acute COVID-19 on cognition 8,9,11,23 . This finding was somewhat in agreement with Zhou et al 13 who reported no significant difference between their patient group and controls in cognitive functions except for continuous and selective attention, and also another study that found no significant difference between the patient group and controls in terms of cognition 24 . Many of the studies that reported impairment in cognitive performance and functions recruited subjects with a history of acute COVID (e.g., 25,26 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also showed that the effects of COVID-19 infection on cognitive performance and functions were weak; a finding that was in disagreement with the former studies that reported significant adverse effects of both mild and acute COVID-19 on cognition 8,9,11,23 . This finding was somewhat in agreement with Zhou et al 13 who reported no significant difference between their patient group and controls in cognitive functions except for continuous and selective attention, and also another study that found no significant difference between the patient group and controls in terms of cognition 24 . Many of the studies that reported impairment in cognitive performance and functions recruited subjects with a history of acute COVID (e.g., 25,26 ).…”
Section: Discussionsupporting
confidence: 92%
“…This finding was somewhat in agreement with Zhou et al . [ 8 ] who reported no significant difference between their patient group and controls in cognitive functions except for continuous and selective attention, and also another study that found no significant difference between the patient group and controls in terms of cognition [ 30 ]. Many of the studies that reported impairment in cognitive performance and functions recruited subjects with a history of acute COVID-19 (e.g.…”
Section: Discussionmentioning
confidence: 99%